Healthcare waste management practices in rural state hospitals, Ampara, Sri Lanka - Kulanga Warnakulahewa; Inoka Suraweera; Prasanga Serasinghe (Journal of the College of Community Physicians)
Introduction: Healthcare waste encompasses all waste generated by healthcare facilities, including that from medical procedures. Approximately 10-25% of healthcare waste is hazardous while 75-90% are non-hazardous. Hazardous waste consists of sharp objects, infectious materials, pharmaceuticals, biological substances, cytotoxic agents, chemicals and radioactive materials. Effective management of healthcare waste involves reducing generation, segregating, collecting, transporting, storing, treating and disposing of it properly. Objectives: To assess healthcare waste management practices and state of related healthcare waste management facilities in rural state hospitals in the Regional Director of Health Services (RDHS) Area, Ampara Methods: A cross-sectional study was conducted in all secondary and primary level state hospitals (n=26) in the health region, Ampara. Data collection utilised observational checklists, desk review of relevant documents and interviews with key persons by using an interviewer-administered questionnaire. Descriptive analysis was conducted using relative frequencies, while significant relationships were evaluated through Chi-squared and Fisher’s exact tests. Results: The research achieved a 100% response rate allowing observations, desk reviews and questionnaire administration in all selected hospitals. Only two hospitals demonstrated satisfactory healthcare waste management practices. None of the hospitals had a proper mechanism to transport healthcare waste. Significant associations were found between the healthcare waste management practices of the hospitals and factors such as the presence of a healthcare waste management plan in the hospital (p=0.02), the existence of a focal point for healthcare waste management activities (p=0.03) and the availability of a mechanism for regular staff training (p=0.04). Conclusions & Recommendations: The study recommends developing healthcare waste management plans, appointing focal points, establishing regular training mechanisms, allocating a separate budget, and forming healthcare waste management committees within hospitals.